2020
DOI: 10.3892/mmr.2020.11067
|View full text |Cite
|
Sign up to set email alerts
|

A novel plasma lncRNA ENST00000416361 is upregulated in coronary artery disease and is related to inflammation and lipid metabolism

Abstract: coronary artery disease (cad) is a serious threat to human health and a major cause of mortality worldwide. long noncoding rnas (lncrnas) affect the occurrence and development of cad via the regulation of cell proliferation and apoptosis, inflammatory responses and lipid metabolism. Screening methods and therapeutic strategies for cad have been extensively studied. The present study analyzed clinical indexes of 187 patients with CAD and 150 healthy subjects. The data showed significant differences in diabetes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…The lncRNA uc003pxg.1 was discovered by lncRNA-seq high-throughput sequencing performed in our previous study ( 22 ). In the present study, the relative expression levels of uc003pxg.1 in PBMCs from 80 patients with CAD and 80 controls were determined by RT-qPCR.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The lncRNA uc003pxg.1 was discovered by lncRNA-seq high-throughput sequencing performed in our previous study ( 22 ). In the present study, the relative expression levels of uc003pxg.1 in PBMCs from 80 patients with CAD and 80 controls were determined by RT-qPCR.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, a number of lncRNAs were identified as differentially expressed in patients with CAD compared with healthy controls through high-throughput sequencing ( 22 ). Among these lncRNAs, the functional lncRNA uc003pxg.1 was demonstrated to function in cell proliferation and migration through high-content analysis in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations